2015
DOI: 10.1007/s10903-015-0219-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Education and Socioeconomic and Occupational Conditions on Self-Perceived and Mental Health Inequalities Among Immigrants and Native Workers in Spain

Abstract: There is limited evidence on the influence of social determinants on the self-perceived and mental health of immigrants settled at least 8 years in Spain. The aim of this study was to examine differences between workers related to migrant-status, self-perceived and mental health, and to assess their relationship to occupational conditions, educational level and occupational social class, stratified by sex. Using data from the Spanish National Health Survey of 2011/12, we computed prevalence, odds ratios and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 8 publications
1
28
0
7
Order By: Relevance
“…Cayuela and colleagues found that settled immigrant women have a higher prevalence of poor self-perceived health (34.6%) and poor mental health (30.1%) than native women (17.7%). The most influential factor in the relationship between health and migrant status for women workers was occupational social class (25% for poor self-perceived health and 17.6% for mental health) and job satisfaction accounted for 15.8% of the difference in self-perceived health [117].…”
Section: Poor Mental Healthmentioning
confidence: 99%
“…Cayuela and colleagues found that settled immigrant women have a higher prevalence of poor self-perceived health (34.6%) and poor mental health (30.1%) than native women (17.7%). The most influential factor in the relationship between health and migrant status for women workers was occupational social class (25% for poor self-perceived health and 17.6% for mental health) and job satisfaction accounted for 15.8% of the difference in self-perceived health [117].…”
Section: Poor Mental Healthmentioning
confidence: 99%
“…Vi utelukket de fleste av studiene grunnet manglende relevans (n = 3 063) i den første screeningen av titler og sammendrag. I alt ble 151 artikler lest i sin helhet, hvor av 92 oppfylte de opprinnelige inkluderingskriteriene (Aalto et al, 2014;Agudelo-Suarez et al, 2013;Agudelo-Suarez et al, 2011;Ahonen & Benavides, 2006;Alexe et al, 2003;Bergbom & Kinnunen, 2014;Bergbom et al, 2015;Bhui et al, 2005;Biering et al, 2016;Borrell et al, 2008;Cayuela et al, 2015;C. Chen et al, 2010;Chowhan, 2016;Connell et al, 2007;Cross & Turner, 2013;Davidson & Orr, 2009;Del Amo et al, 2011;Diaz-Serrano, 2013;Dunlavy et al, 2016;Dunlavy & Rostila, 2013;Elders et al, 2004;Font, Moncada, Llorens, et al, 2012;Frickmann et al, 2012;Gil-Gonzalez et al, 2014;Hogh et al, 2011;Hoppe, 2011;Johansson et al, 2012;Jonson & Giertz, 2013;Jorgensen et al, 2011;Krings et al, 2014;Kuusio et al, 2013;Mastrangelo et al, 2010;Miller & Travers, 2005;Nieuwenhuijsen et al, 2015;Olesen et al, 2012a;Olesen et al, 2012b;Pasca & Wagner, 2012;Perez-Carceles et al, 2014;…”
Section: Resultaterunclassified
“…Studier som har undersøkt hvorvidt helseproblemer er mer utbredt blant sysselsatte innvandrere enn hos øvrige sysselsatte (forskningsspørsmål 2A) har vurdert følgende helseindikatorer: selvrapportert helse SRH) og symtomer på dårlige psykiske helse (n = 17), sykefravaer og uførepensjonering (n = 12) og arbeidsskader (n = 16). Blant de 45 studiene var det ni studier som undersøkte om forskjeller knyttet til arbeidsmiljøet kan bidra til å forklare (mediere) sammenhengen mellom innvandrerstatus og helseproblemer (forskningsspørsmål 2B) (Cayuela et al, 2015;Dunlavy & Rostila, 2013;Nieuwenhuijsen et al, 2015) eller sykefravaer og uførepensjonering Sole et al, 2013).…”
Section: Helse Sykefravaer/uførhet Og Arbeidsskadeunclassified
See 2 more Smart Citations